2019
DOI: 10.3201/eid2508.190112
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamily Transmission of Monkeypox Virus, Central African Republic, 2018

Abstract: Monkeypox is a rare viral zoonotic disease; primary infections are reported from remote forest areas of Central and West Africa. We report an investigation of a monkeypox outbreak in Lobaye, southwest Central African Republic, in October 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 8 publications
1
86
0
2
Order By: Relevance
“…In Nigeria or Sierra Leone, human cases more likely correspond to indigenous zoonotic spillover than to importation from a neighboring country 14 , 54 . Although three modes of transmission (familial, health care-related and transport-related) were identified during the small outbreak that occurred in Bangassou in 2016 11 , human-to-human transmission in CAR is generally confined to a single family 55 . It rarely spreads over long distances, with the exception of the street vendor from Ippy who probably infected his girlfriend in the town of Rafaï, several hundred kilometers away.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria or Sierra Leone, human cases more likely correspond to indigenous zoonotic spillover than to importation from a neighboring country 14 , 54 . Although three modes of transmission (familial, health care-related and transport-related) were identified during the small outbreak that occurred in Bangassou in 2016 11 , human-to-human transmission in CAR is generally confined to a single family 55 . It rarely spreads over long distances, with the exception of the street vendor from Ippy who probably infected his girlfriend in the town of Rafaï, several hundred kilometers away.…”
Section: Discussionmentioning
confidence: 99%
“…Monkeypox data from the DRC accounted for approximately one-third of the eligible articles [5,13,14,[16][17][18][19][20][21][22][23][24][25][26][27][28]. The remaining articles had monkeypox data from the CAR [29][30][31][32][33][34][35], United States (US) [36][37][38][39][40][41], Nigeria [5,[42][43][44], Republic of the Congo [15,[45][46][47], Sierra Leone [42,48,49],…”
Section: Number Of Reports By Countrymentioning
confidence: 99%
“…Details are presented in S3 Table . A review of these articles did not establish any evolution in SAR over time. More than half of the articles (9/16) reported an SAR of 0% [8,23,30,42,[49][50][51][52]57], and this spanned the decades from the 1970s through 2010-2019. Similarly, over those same five decades, the SAR ranged from 0.3-10.2% in 6/16 articles [5,14,20,22,54,56].…”
Section: Secondary Attack Ratementioning
confidence: 99%
See 1 more Smart Citation
“…In the last week of October, another relative of this index case female was reported to have contracted the disease. In this investigation, it was observed that the disease spread among the index case female's family members and relatives through three waves of infection and hence was considered as an intrafamilial transmission of MPXV disease [168].…”
Section: Central African Republicmentioning
confidence: 99%